2022
DOI: 10.53092/duiibfd.1031256
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Patient-Centered Communication and Service Quality: The Mediator Effect of Trust in the Service Provider

Abstract: Hasta merkezli iletişim, hasta merkezli bakımın temelinde yer alan önemli bir kavramdır. Hasta merkezli iletişim, hekimin hastaların ihtiyaçlarını anlamasını, hastalara yeterli bilgi vermeyi ve hastalar ile hekim arasında güven oluşturmayı amaçlayan önemli bir iletişim tarzıdır. Hasta merkezli iletişimin; hasta memnuniyeti, hastanın kalite algısı, hastanın tedaviye katılımı, hasta ve hekim arasında güvenin tesis edilmesi ve klinik sonuçlar üzerinde olumlu etkilerinin olduğu ortaya koyulmuştur. Bu çalışmada, ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
1
1
0
1
Order By: Relevance
“… 71 According to the results of a study conducted with the data of 261 patients who applied to a physical therapy and rehabilitation outpatient clinic in Turkey, patient-centered communication was found to increase trust in physicians and positively affect service quality. 72 A similar result was revealed in the study conducted by Eptesin et al In the study, it was reported that patient-centered communication has an important function in the perception of high quality health services. Reynolds (2009) reported that patient-centered communication has a significant effect on patient satisfaction, which in turn has a significant effect on service quality.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“… 71 According to the results of a study conducted with the data of 261 patients who applied to a physical therapy and rehabilitation outpatient clinic in Turkey, patient-centered communication was found to increase trust in physicians and positively affect service quality. 72 A similar result was revealed in the study conducted by Eptesin et al In the study, it was reported that patient-centered communication has an important function in the perception of high quality health services. Reynolds (2009) reported that patient-centered communication has a significant effect on patient satisfaction, which in turn has a significant effect on service quality.…”
Section: Discussionsupporting
confidence: 77%
“…77 In particular, many studies have reported that patient-centered communication improves patient care processes and positively affects the quality of care received by patients. 60 , 72 , 77 - 81 Uncertainty negatively affects the quality of health services received. 82 Therefore, it is stated that the perceived health care quality perception increases with the increase in patients’ ability to cope with uncertainty.…”
Section: Discussionmentioning
confidence: 99%
“…Aksine hastaların kalite algıları pozitif yönde geliştiğinde, hissettikleri memnuniyet düzeyleri de bu gelişmeden olumlu şekilde etkilenmektedir. Hastaların hizmet kalitesiyle alakalı algıladıkları olumlu durum, hizmet aldığı sağlık kurumunu yakınlarına tavsiye etme, ihtiyaç halinde aynı sağlık kurumunu ve aynı hekimi yeniden tercih etme davranışlarını da olumlu şekilde etkileyebilmektedir (Çakmak ve Uğurluoğlu, 2022;Öz ve Uyar, 2014). Hizmet sunumunda hastaların kalite algılarının oluşmasında personel davranışları önemli bir etkendir.…”
Section: Introductionunclassified